Firm ownership, institutional environment and agricultural innovation: evidence from China - Qionghua Li; Junyan Zhang; Xiumin Jiang (Cogent Business & Management)
The relationship between firm ownership and innovation is a critical academic topic. Although agriculture is pivotal to emerging economies, empirical evidence on how internal institutions (firm ownership) and the external institutional environment jointly influence innovation in this sector remains limited. Based on the resource-based view and institutional theory, this study develops an integrated analytical framework linking firm ownership and institutional environment to agricultural innovation. The framework is tested using an unbalanced panel of 117 Chinese agricultural listed firms during 2004–2022, employing firm-fixed-effects models and multiple robustness checks. The findings reveal that: (1) Agricultural state-owned enterprises (SOEs) demonstrate the highest innovation performance, especially those controlled by the central government. (2) However, in China’s major grain-producing regions and seed industry, the innovation performance of SOEs was not superior to that of private enterprises. (3) Improvements in the institutional environment positively moderate the relationship between firm ownership and agricultural innovation. This study enriches the literature on institutional economics and corporate innovation and deepens the understanding of innovation mechanisms in emerging economies. It also provides valuable policy implications for governments acting as patient investors, balancing multiple roles, optimizing the institutional environment, and offering differentiated support.